La Casa del Estudiante Ernesto “Che” Guevara, un ejemplo de pluralismo jurídico - Sánchez García, Erika Myriam (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
The actual work has as object of study and analyze the refuge known as “Ernesto Che Guevara” student shelter, using for this the theoretical basis propounded by the contemporary conception of legal pluralism, in reason that this concept it is more in accordance with the diversity of practices that exist in the same place or social field, and the way they interact with each other or when that practices come into conflict with the officials regulations. The Ernesto Che Guevara student shelter it´s a social field who has with its own norms of operation, this rules are different from the regulation of the Universidad Michoacana de San Nicolás de Hidalgo and so, these norms could confront the University´s rules.

El presente escrito tiene como objeto estudiar y analizar a la Casa del Estudiante “Ernesto Che Guevara” empleando para esto el marco teórico propuesto por la actual concepción del pluralismo jurídico, en razón de que está más acorde con pluralidad de prácticas existentes en un mismo espacio o campo social, y que pueden interactuar o entrar en conflicto con las normas jurídicas oficiales. La Casa del Estudiante Ernesto Che Guevara es un campo social que cuenta con sus propias normas de operación, que difieren y pueden entrar en confrontación con las dispuestas en la normatividad de la Universidad Michoacana,
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2016-0359; Humanidades; Sociología jurídica; Prácticas sociales; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/723